THE EFFECTIVENESS OF YOUGLISH WEBSITE IN IMPROVING STUDENTS' VOCABULARY AT SMPN SATAP 2 PASIR PUTIH MUNA (Karya Ilmiah Mahasiswa (KIMA), 2024)
The focus of this research was the use of YouGlish in improving students’ vocabulary at SMPN Satap 2 Pasir Putith Muna. YouGlish is a website that offers a variety of captivating materials with subtitles that are freely accessible. Most of the videos are from YouTube videos, so students can learn English vocabulary and phrases in a practical and fun way. The purposes of this research are to investigate the effectiveness of the use of the YouGlish website at SMPN Satap 2 Pasir Putih Muna and to explore the students’ perceptions about the use of the YouGlish website in improving students’ vocabulary at SMPN Satap 2 Pasir Putih Muna. The method used in this research was Classroom Action Research (CAR), which had two cycles and threemeetings per cycle. Planning, implementing, observing, and reflecting are all parts of the research process. The results showed that the mean score on the pre-test was 56.75, and there were no students who achieved the minimal criteria, the mean score on the first cycle test was 61.25, and there were 35% of the students have reached the minimal criteria of success, and the mean score on the second cycle test was 78.5, and 80% of the students have reached the minimal criteria of success, that means the students have improved their vocabulary abilities in each test. Based on the results of the tests and the questionnaire were given, most of the students are agree that the YouGlish website can improve their vocabulary abilities.